Wiley Encyclopedia of Chemical Biology 2008
DOI: 10.1002/9780470048672.wecb407
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acids: Hydration

Abstract: Water is an integral part of DNA structure, and it plays an important role in dictating conformational preferences and binding properties of nucleic acids. Although in recent years a wealth of information on the physical properties of water in the vicinity of nucleic acids has accumulated, our understanding of how water interacts with nucleic acids and how it mediates DNA recognition by small ligands and DNA‐binding proteins remains limited. In this article, we review the current state of DNA hydration researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…According to Le Châtelier's principle, this leads to an overall decrease in the volume of the system upon dissociation of the droplet phase by pressure (Figure 5), which is also favored by a higher mixing entropy. Differential changes in protein surface hydration could make an additional contribution, [40] which is probably of minor importance here. Of note, void volumes can also arise from imperfect packing in folded structures of globular proteins, but these unfold at much higher pressures, typically between ∼4 and ∼8 kbar [39] …”
Section: Discussionmentioning
confidence: 92%
“…According to Le Châtelier's principle, this leads to an overall decrease in the volume of the system upon dissociation of the droplet phase by pressure (Figure 5), which is also favored by a higher mixing entropy. Differential changes in protein surface hydration could make an additional contribution, [40] which is probably of minor importance here. Of note, void volumes can also arise from imperfect packing in folded structures of globular proteins, but these unfold at much higher pressures, typically between ∼4 and ∼8 kbar [39] …”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have indicated that 10 to 30 water molecules per phosphate are involved in the interaction with DNA 30 . The hydrating properties of nucleic acids suggest that PN can be beneficial for individuals with dry skin that has weakened scaffolding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that 10 to 30 water molecules per phosphate are involved in the interaction with DNA. 30 The hydrating properties of nucleic acids suggest that PN can be beneficial for individuals with dry skin that has weakened scaffolding. Also, PN serve as both barrier organelles and structural scaffolds that support the proper accumulation of ECM during the process of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by differences in the hydration of A-DNA and B-DNA. It is known that the A-form of DNA is formed in lower hydration conditions than B-form DNA [29][30][31][32][33][34]. However, in A-DNA the main hydrated water molecules are concentrated on strongly polar oxygens of phosphate groups and form water chains along the DNA chain [31,32].…”
Section: The Thermodynamics Of Binding Of Porphyrins With A-and B-formentioning
confidence: 99%
“…Water bound on phosphate groups does not form a similar lattice in the major groove of B-DNA. The B-form of DNA is stabilized by a water backbone formed by water molecules from the first hydration layer of AT-rich regions of the DNA minor groove [33,34]. Therefore it can be concluded that the major groove of A-DNA is hydrated more intensly than the major groove of B-DNA.…”
Section: The Thermodynamics Of Binding Of Porphyrins With A-and B-formentioning
confidence: 99%